Реалізація системи контролю температури двигуна в електроприводі змінного струму - Гузенко, Віталій Вікторович; Галько, Сергій Віталійович; Чаусов, Сергій Володимирович; Сорокін, Максим Сергійович; Хандола, Юрій Миколайович; Huzenko, Vitalii; Halko, Serhii; Chausov, Serhii; Sorokin, Maxim; Khandola, Yurii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті аналізуються нестаціонарні теплові процеси електричних машин, побудована проста математична модель для розрахунку температури статорної обмотки в асинхронному двигуні. Проаналізовано систему контролю температури обмотки двигуна. Експериментально досліджені температурні процеси у двигуні при складних режимах його роботи. Зазначено, що результати розрахунку за спрощеною моделлю теплового динамічного процесу значно відрізняються від експерименту, що підтверджує необхідність контролю температури обмоток двигуна та реальний час для параметричної корекції системи векторного управління електроприводом змінного струму. /// EN: The purpose of this article is to build a model of a robotic mobile platform capable of navigating rough terrain. The article describes the components required to assemble a mobile robotic platform based on the Arduino Mega. Connection diagrams for the device’s main electronic components are provided. A description of the connections for the device’s main electronic components is provided. A modification of the electric drive is described that will allow this electronic component to be adapted to the task at hand. This article analyzes the transient thermal processes of electric motors and constructs a simple mathematical relationship for calculating the temperature parameters of the stator winding in an electric machine. A motor winding temperature control system is analyzed. Transient processes in the motor are investigated, and the results are experimentally confirmed under challenging operating conditions. It is shown that the calculation results, based on a simplified thermodynamic process relationship, differ significantly from the experimental results, demonstrating the need for real-time monitoring of the electric motor winding temperature for transient correction of the vector control system of an asynchronous AC drive. In this paper, we focused on the DS18B20 digital temperature sensor to address the problem of researching and constructing a temperature control system. The study of the electromechanical system at the nominal speed of rotation and 50 % of the nominal load observed an excess of the stator temperature by 10° C (time constant of the process 400s). At a rotor rotation speed of 0.3 nm and a 50 % nominal load, the value of the stator temperature overshoot by 40°C (process time constant 280 s), stator coil by 85 °C (process time constant 200 s). The obtained calculations, which were based on the required characteristics of the temperature process, differed significantly from the experimental results, which confirms the importance of monitoring the temperature of the electric motor windings under real conditions.
Implementation of engine temperature control system in ac electric drive
Keywords: асинхронний електродвигун; електропривод; математична модель; аграрно-промисловий комплекс; температурні процеси; asynchronous electric motor; electric drive; mathematical model; agro-industrial complex; temperature processes